Ampithoe bizseli n. sp. (Crustacea, Amphipoda) from the west coast of Turkey - Özaydinli, Murat; Coleman, Ch. Oliver (Zootaxa, 2012)
The new species Ampithoe bizseli from the west coast of Turkey is described. It can be distinguished by a circular ischiumlobe on gnathopod 2 in the male sex from the similar species Ampithoe ramondi where this lobe is slender. Ampithoe bizseli n. sp. appears to occur also on the coast of Tansania.